The Effectiveness of Using Tajwid Rule Flashcards on the Cognitive Abilities of Junior High School Students - Annur, Najma; Fitriani; Marwiyah, St.; Zainuddin, Fauziah (Journal of Social and Scientific Education, 2024)
This research aims to assess the significant differences in cognitive abilities among students before and after using the flashcard media for the rules of Tajwid in Islamic Education classes for eighth-grade students in junior high school and to evaluate the effectiveness of using flashcards for Tajwid rules on students' cognitive abilities in Islamic Education classes for eighth-grade students in junior high school. This research employs a quantitative pre-experimental approach with a one-group pre-test and post-test model. The sample was selected using a purposive sampling technique, involving 16 eighth-grade students with specific considerations. Data were collected through learning outcome tests, which were then analyzed using descriptive and inferential statistics. The results of descriptive analysis indicate an improvement in students' learning outcomes after using flashcards for Tajwid rules, as reflected in the increased average scores of written and oral tests from pre-tests to post-tests. Inferential analysis shows the effectiveness of using flashcards for Tajwid rules on students' cognitive abilities, as evidenced by the results of hypothesis testing. The n-gain test also indicates that the use of flashcards for Tajwid rules can be categorized as "fairly effective" with an average increase in n-gain scores of 56.9746% for written tests and 56.2785% for oral tests.